Infection Control Knowledge, Attitudes, and Practices among Healthcare Workers at Mulago Hospital, Kampala, Uganda - Sethi, Ajay K.; Acher, Charles W.; Kirenga, Bruce; Mead, Scott; Donskey, Curtis J.; Katamba, Achilles (Infection Control & Hospital Epidemiology, 2012)
Effective implementation of infection control programs and adherence to standard precautions are challenging in resource limited settings. The objective of this study was to describe infection control knowledge, attitudes, and practices among healthcare workers (HCWs) in Uganda. DESIGN. We conducted a survey of hospital employees who had direct contact with patients or their immediate environment. We also performed an environmental assessment of resource availability and utilization within hospital wards. SETTING. Surgical, medicine, and obstetrics wards at a national referral hospital in Kampala, Uganda. PARTICIPANTS. One hundred eighty-three randomly selected HCWs. RESULTS. Almost all HCWs knew to wash their hands, although nursing and support staff were less likely to perceive that HCWs' hands can be a vector of disease transmission. Hand washing was valued more as a means of self-protection than as a means to prevent patientto-patient transmission, consistent with the prevailing belief that infection control was important for occupational safety. Sinks were not readily accessible, and soap at sinks was uncommon throughout the medicine and obstetrics wards but more commonly available in the surgery wards. Alcohol gel was rarely available. CONCLUSIONS. Changing infection control practices in developing countries will require a multifaceted approach that addresses resource availability, occupational safety, and local understanding and attitudes about infection control.
Keywords: Infection Control Knowledge; Attitudes; Practices; Healthcare Workers; Mulago Hospital